Perlindungan Konsumen Terhadap Keterlambatan Penyerahan Rumah - Riana Shabrina; Aminah Aminah (Notarius, 2022)
AbstractAlong with the continuous increase in the population in Indonesia, the availability of various facilities that support life has also increased. This is what encourages the Government and the private sector to always create innovations to meet the needs of the community in the field of development, especially residential buildings, but in buying and selling between the consumer and the developer, the developer defaults, causing a dispute related to the delay in the delivery of the house building by the parties. developers. This study examines consumer protection in the event of a delay in the delivery of housing units by the developer. In analyzing the author uses the type of empirical juridical research and is descriptive analytical and the legal basis refers to the UUPK. Consumer rights have been partially protected and can be said not to be comprehensive, in the process through legal channels, the Judge's consideration in this decision only confirms the BPSK decision regarding the fulfillment of consumer rights because the decision has made a pledge. In this case, the consumer's rights have been protected by UUPK although not comprehensively, both in terms of getting compensation, compensation and/or replacement due to goods and/or services received not properly.Keywords : consument protection; default; buying and selling housesAbstrakSeiring dengan peningkatan jumlah penduduk di Indonesia yang berlangsung terus menerus maka ketersediaan berbagai fasilitas yang mendukung kehidupan juga mengalami peningkatan. Hal ini yang mendorong pihak Pemerintah maupun Swasta untuk selalu menciptakan inovasi untuk memenuhi kebutuhan masyarakat di bidang Pembangunan khususnya Bangunan Rumah Tinggal, akan tetapi dalam jual beli antara pihak konsumen dengan developer, pihak developer melakukan wanprestasi sehingga menimbulkan persengketaan terkait adanya keterlambatan penyerahan bangunan rumah oleh pihak developer. Penelitian ini mengkaji mengenai Perlindungan Konsumen apabila terjadi keterlambatan dalam penyerahan unit rumah oleh pihak developer. Dalam menganalisa penulis menggunakan tipe penelitian yuridis empiris dan bersifat Deskriptif Analitis serta landasan hukumnya mengacu pada UUPK. Hak konsumen telah dilindungi sebagian dan dapat dikatakan tidak secara menyeluruh,dalam proses melalui jalur hukum,  Pertimbangan Hakim dalam putusan ini hanya menegaskan putusan BPSK terkait pemenuhan hak konsumen karena putusan tersebut sudah ikrar. Dalam hal ini hak konsumen telah dilindungi oleh UUPK walaupun tidak secara menyeluruh baik dalam hal mendapatkan kompensasi, ganti kerugian dan/atau penggantian akibat barang dan/atau jasa yang diterima tidak sebagaimana mestinya.Kata kunci : perlindungan konsumen; wanprestasi; jual beli rumah